COMPARISON OF BLEEDING COMPLICATIONS BETWEEN TURP AND OPEN PROSTATECTOMY IN PATIENT WITH BPH - Limantara, Ancelia; Soebadi, Doddy M; Pramesti, MP Budyandini D; Rizaldi, Fikri (Indonesian Journal of Urology, 2019)
Objective: Benign prostatic hyperplasia (BPH) is the enlargement of prostate glands. Two commonly used methods of BPH surgery in Indonesia are transurethral resection of prostate (TURP) and open prostatectomy. International studies have shown both methods have bleeding complications, occurring in 7% in TURP and 22% in open prostatectomy. But, only few researches for bleeding during BPH surgery are done in Indonesia. This study aimed to analyze the difference in bleeding complications between TURP and open prostatectomy in Indonesia. Material & Methods: An observational study with cross-sectional design, using consecutive sampling from medical records of patients above 21 years old with BPH who came to Poli Urologi Soetomo Hospital in 2015–2016 for TURP or open prostatectomy. Data were analyzed using Fischer and Mann-Whitney. Results: Information was obtained from 62 patients, TURP was done in 49 patients (79.03%) and 13 patients (26.53%) in which had bleeding complication. Open prostatectomy was done in 13 patients (20.97%) and 6 patients (46.15%) in which had bleeding complications. Fischer test showed no significant difference in bleeding complications between TURP and open prostatectomy in patients with BPH (p=0.192), including patients with urine retention (p=0.451), without urine retention (p=0.249), age below 70 (p=0.140) and above 70 (p=1). Mann-Whitney test showed significant difference in bleeding complications volume between TURP and open prostatectomy (p=0.012). Conclusion: There was no significant difference in bleeding complications between TURP and open prostatectomy in patients with BPH. But, between TURP and open prostatectomy significant difference in bleeding volume was found.